O papel da desaprendizagem em fusões de empresas: uma revisão sistemática de literatura - Roberto, Terena Moraes (Universidade Federal de São Carlos, 2025)
When organizations are in the process of merging, there is a background of instability and a business context that will undergo several changes in its processes, organizational culture and knowledge about how to carry out each stage of production of its products or services, and with this comes the process of abandoning old practices that no longer fit in the new company that is being created, a process known as unlearning. This paper aims to conduct a systematic literature review (SLR) of what has already been published on unlearning - individual or organizational - in merger scenarios between companies. As a result of the RSL carried out on the Web of Science (Clarivate Analytics), Spell and Scielo databases, it was possible to observe the aspects resultant from the unlearning process in merger environments, mainly from an internal perspective, focusing on how employees experienced it.
The role of unlearning in company mergers: a systematic literature review
Keywords: Desaprendizagem Individual; Desaprendizagem Organizacional; Fusão de Empresas; Individual Unlearning; Organizational Unlearning; Company Mergers; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS